Identification of copper related biomarkers in breast cancer using machine learning - Jing Wang; Haining Wang; Zilan Li; Qi Xu; Yiwei Yang; Run Shi; Feng Liu; Shiyang Jin (Discover Oncology)
Abstract Background Breast cancer is the most prevalent and deadly cancer among women globally, necessitating more effective diagnostic and therapeutic approaches. This study aims to explore new treatment targets and diagnostic tools. Methods Employing machine learning techniques and utilizing PCR, IHC technologies, and multiple databases, we identified and validated genes closely linked with breast cancer and copper-induced cell death. We then explored how their expression levels impact cancer diagnosis, prognosis, immune cell infiltration, and drug sensitivity. Results This investigation identified three crucial genes—MT1M, GRHL2, and PKM—intimately associated with the copper death mechanism in breast cancer pathology. Validated through comprehensive analysis across cells, tissue models, and diverse databases, these genes showed significant differential expression (P-value < 0.05), affirming their pivotal role in enhancing diagnostic accuracy (AUC values: 0.917, 0.970, 0.951) and prognostic assessment (HR = 0.65, P = 0.018; HR = 1.69, P = 0.0011; HR = 1.51, P = 0.012) in breast cancer. Additionally, their expression levels influence the infiltration of immune cells and the sensitivity to certain drugs. Conclusion MT1M, GRHL2, and PKM are novel diagnostic and therapeutic targets for breast cancer. These findings enhance prognostic evaluations, deepen our understanding of its mechanisms.